2019
DOI: 10.3389/fphys.2019.00575
|View full text |Cite
|
Sign up to set email alerts
|

Multi-System Adaptation to Confinement During the 180-Day Controlled Ecological Life Support System (CELSS) Experiment

Abstract: Confinement experiments are essential to prepare long-term space exploration. The 180-day Chinese CELSS (Controlled Ecological Life Support System) study is unique in its design, including a closed-loop system and mid-mission simulation of Mars-like day–night cycle of 24 h 40 min for 36 days (days 72–108). Our aim was to study physiological and psychological consequences of this confinement in four healthy volunteers (one female). CELSS platform consisted of six interconnected modules including four greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
2
27
2
Order By: Relevance
“…Segmental inactivity models are also used, with unilateral lower limb suspension ( Bleeker et al, 2005a , c ) and limb casting ( Green et al, 1997 ; Sugawara et al, 2004 ) being less extreme models. Although confinement has also been considered a model of spaceflight ( Arbeille et al, 2014 ; Yuan et al, 2019 ), its associated inactivity is difficult to attest.…”
Section: Introductionmentioning
confidence: 99%
“…Segmental inactivity models are also used, with unilateral lower limb suspension ( Bleeker et al, 2005a , c ) and limb casting ( Green et al, 1997 ; Sugawara et al, 2004 ) being less extreme models. Although confinement has also been considered a model of spaceflight ( Arbeille et al, 2014 ; Yuan et al, 2019 ), its associated inactivity is difficult to attest.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [26] showed that body weight decreased (mainly lean mass) on the 6th month during the isolation environment. We found that concentration of TP as well as GLB also reduced on 175 th day.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, NASA has been using its Human Exploration Research Analog (HERA) facility at Johnson Space Center to investigate the effects of isolation and confinement for up to 45 days 24 . Except for several Russian studies using the NEK complex [19][20][21] , and Chinese experiments in Chinese CELSS (Controlled Ecological Life Support System) 25 , laboratory-based isolation studies in isolated, controlled and confined analogs (ICC) have often been rather short in duration (<60 days). Submariners and Antarctic stations can provide excellent opportunities to study the effects of prolonged isolation and confinement in real extreme environments (isolated, confined and extreme environments, ICE).…”
Section: History Of Isolation Experimentsmentioning
confidence: 99%